2013
DOI: 10.1016/j.aquatox.2013.02.012
|View full text |Cite
|
Sign up to set email alerts
|

Detecting genome-wide gene transcription profiles associated with high pollution burden in the critically endangered European eel

Abstract: a b s t r a c tThe European eel illustrates an example of a critically endangered fish species strongly affected by human stressors throughout its life cycle, in which pollution is considered to be one of the factors responsible for the decline of the stock. The objective of our study was to better understand the transcriptional response of European eels chronically exposed to pollutants in their natural environment. A total of 42 pre-migrating (silver) female eels from lowly, highly and extremely polluted env… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 48 publications
1
14
0
Order By: Relevance
“…The data were reported for different fish species and ranged from <0.001 μg/kg ww in nearnatural Irish waters to 25 μg/kg ww in the Netherlands. Even higher values from Dutch waters were reported from Pujolar et al [21] who measured a mean concentration of 92 μg/kg ww (sum of ten PBDEs) in female silver eels from the highly polluted Dessel Schoten Canal. Sühring et al [22] analysed nine PBDEs in silver eels from the upper part of the Rhine and found a mean concentration of 21.3 μg/kg.…”
Section: Introductionmentioning
confidence: 71%
See 1 more Smart Citation
“…The data were reported for different fish species and ranged from <0.001 μg/kg ww in nearnatural Irish waters to 25 μg/kg ww in the Netherlands. Even higher values from Dutch waters were reported from Pujolar et al [21] who measured a mean concentration of 92 μg/kg ww (sum of ten PBDEs) in female silver eels from the highly polluted Dessel Schoten Canal. Sühring et al [22] analysed nine PBDEs in silver eels from the upper part of the Rhine and found a mean concentration of 21.3 μg/kg.…”
Section: Introductionmentioning
confidence: 71%
“…Several studies tried to relate the contaminant burden of eels to enzymatic activity and transcriptomic responses. Pujolar et al [21] found a correlation for the up-regulation of the transcription of genes associated with detoxification and a down-regulation of the transcription of genes associated with the oxidative phosphorylation pathway in eels with a PCB burden comparable to many North Rhine-Westphalian sites. Kammann et al [36] investigated the ethoxyresorufin-O-deethylase (EROD) activity in eels from the Elbe and found that the EROD activity corresponded to PAH metabolite concentration in eel bile and to pollution levels from the sampling sites.…”
Section: Pcdds Pcdfs and Indicator Pcbsmentioning
confidence: 99%
“…In this view, it is interesting to note that some discrepancies appear between our work and previous field transcriptomic studies. For example, in the studies carried out by (Pujolar et al 2012(Pujolar et al , 2013, during which the transcriptome of eels from a clean site was compared with the transcriptome of eels from polluted sites by means of DNA microarray, significant changes in the transcription level of genes involved in detoxification, in the fight against oxidative stress and in the general stress response (e.g. metallothioneins, heat shock proteins) were observed.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, it is not surprising that RNA-seq has become the technology of choice for quantifying differential gene expression (Deng et al, 2011;Smith et al, 2013). Gene expression analyses have allowed the identification of key molecular mechanisms underlying desired traits in farmed fish (Roberge et al, 2006;Ferraresso et al, 2008Ferraresso et al, , 2013, but have also been successfully applied to natural populations of marine fishes (Whitehead and Crawford, 2006;Larsen et al, 2007Larsen et al, , 2011Pujolar et al, 2012Pujolar et al, , 2013bCôté et al, 2014). Finally, transcriptomic analyses can be complemented and integrated with protein expression analysis to investigate the responses at the proteomic level for a deeper understanding of functional implications (Nie et al, 2007;Dalziel and Schulte, 2012).…”
Section: Linking Genotype and Phenotypementioning
confidence: 99%